Effect of age and level of damage on the autogenous healing of lime mortars. (1st September 2017) - De Nardi, C.; Cecchi, A.; Ferrara, L.; Benedetti, A.; Cristofori, D.
Abstract: Natural hydraulic lime-based mortars are recommended for retrofitting operations in historical buildings, primarily because of their high chemical, physical and mechanical compatibility with the existing ones; moreover, their autogenous and engineering self-healing capacities make them a more suitable material for the aforementioned interventions. This work proposes a methodology to quantify the autogenous self-healing in terms of recovery of the compression strength and ultrasonic pulse velocity in samples made of natural hydraulic lime mortars; specimens were pre-cracked at different ages (14–84 days) and levels of damage (70% of the compression strength in pre-peak regime; 90% of the compression strength in post-peak regime), and then cured under water up to 28 days. The capacity of healing after two loading/healing cycles has been also investigated. An interdisciplinary approach has been pursued characterising the mechanical aspects of the healing and the chemical nature of the products via SEM/EDS analyses. The results provide useful indication about the dependence of the self-healing capacity on the aforementioned variables.